2021
DOI: 10.1007/s00418-021-02016-6
|View full text |Cite
|
Sign up to set email alerts
|

Porcine ovarian cortex-derived putative stem cells can differentiate into endothelial cells in vitro

Abstract: Endothelial cells (ECs), the primary component of the vasculature, play a crucial role in neovascularization. However, the number of endogenous ECs is inadequate for both experimental purposes and clinical applications. Porcine ovarian putative stem cells (poPSCs), although not pluripotent, are characterized by great plasticity. Therefore, this study aimed to investigate whether poPSCs have the potential to differentiate into cells of endothelial lineage. poPSCs were immunomagnetically isolated from postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Among various animal experimental models, pigs share many similarities with humans in the form of organ size, physiology, and functioning [ 31 ]. The limited ethical dilemmas and importantly, successful isolation of putative stem cells from the ovarian cortex (poPSCs) [ 32 , 33 , 34 ], make pigs the valuable experimental model for not only preclinical assessment for stem cell therapy but also for the purposes of somatic cell nuclear transfer (SCNT)-based cloning in mammals. The efforts undertaken to use poPSCs, which have been subjected to extrinsic anabolic steroid-dependent oncogenic transformation (carcinogenesis), as a completely new source of nuclear donor cells (NDCs) for future research focused on SCNT, have not yet been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Among various animal experimental models, pigs share many similarities with humans in the form of organ size, physiology, and functioning [ 31 ]. The limited ethical dilemmas and importantly, successful isolation of putative stem cells from the ovarian cortex (poPSCs) [ 32 , 33 , 34 ], make pigs the valuable experimental model for not only preclinical assessment for stem cell therapy but also for the purposes of somatic cell nuclear transfer (SCNT)-based cloning in mammals. The efforts undertaken to use poPSCs, which have been subjected to extrinsic anabolic steroid-dependent oncogenic transformation (carcinogenesis), as a completely new source of nuclear donor cells (NDCs) for future research focused on SCNT, have not yet been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed according to a technique developed and modified in our laboratory [ 41 ]. Briefly, after the termination of both poPSC cultures treated and not treated with AASs for 7 or 14 days, they were washed twice with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the large diversity of ovarian ASCs, they are also called putative stem cells (PSCs) [ 37 , 38 , 39 ]. The results of our previous studies [ 37 , 40 , 41 ] have demonstrated that porcine ovarian putative stem cells (poPSCs) isolated from the ovarian cortex (against the presence of SSEA-4 antigen), though the non-specific expression of selected pluripotency markers are not pluripotent but rather multipotent. We have shown that poPSCs can differentiate into functional neural-like and endothelial cells, poPSCs likely represent just multipotent mesenchymal stem cell (MSCs) populations in the ovary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the need for a source of endothelial cells for tissue engineering and human regenerative medicine, the porcine model, which as mentioned above has been used previously for many xenogeneic procedures (see also for instance Gasek et al 2021), appeared to represent a potential source for these cells. This led Wartalski et al (2021) to extend their recent studies to investigate whether the multipotent high-plasticity poPSCs could also be directed to differentiate into endothelial-lineage cells. They isolated poPSCs from porcine ovarian cortex using an immunomagnetic approach with anti-SSEA-4 conjugated to the magnetic beads.…”
Section: Differentiation Of Porcine Ovarian Mesenchymal Stem Cells Into Endothelial Cellsmentioning
confidence: 99%